Biologicals in the treatment of psoriasis: The Indian perspective - Ajit B Janagond; Aparna Palit (Wolters Kluwer Medknow Publications, 2017)
Psoriasis is a common inflammatory skin disorder characterized by itchy erythematous papules and plaques topped with silvery white scales. It has a chronic relapsing course and is associated with significant morbidity and reduction in the quality of life. Therapy of psoriasis is challenging. Topical therapy forms the first line of treatment for stable plaque psoriasis affecting a limited body surface area and in extensive disease systemic agents are indicated. All these drugs have inherent side effects, and none bring prolonged remission of the disease. The other therapeutic modality for psoriasis is phototherapy, but it is delivered through a specialized machine which can be available only at referral centers. Biologics have revolutionized the management of psoriasis as they can bring a remission of disease up to several years. Although limited availability and high cost prohibit their regular usage, Indian dermatologists are rapidly adopting biologics in the treatment of psoriasis.